Expression of p21ras in normal and malignant human tissues: lack of association with proliferation and malignancy. - Chesa, P G (1987)
Proteins encoded by cellular ras oncogenes (p21ras) are expressed in a wide variety of malignant tumors, including carcinomas, lymphomas, and neuroectodermal tumors. The function of p21ras in these tumors and the distribution and role of p21ras in corresponding normal tissues are unclear. This immunohistochemical study examined the relationship between p21ras expression and malignant transformation, cellular differentiation, and proliferative activity in vivo. p21ras was found to be widely expressed in normal tissues, but within those tissues expression was often sharply restricted to cells at specific stages of differentiation; terminally differentiated cells generally showed stronger reactivity with antibodies to p21ras than did rapidly proliferating cells. Fetal and adult tissues had corresponding patterns of p21ras expression, and the distribution of p21ras in neoplasms paralleled the pattern in normal tissue from which they were derived. Thus, p21ras seems to play a role in many fully differentiated cell types, and levels of p21ras expression do not correlate with proliferative activity in normal cell or, in contrast to past reports, with the transformed phenotype.